Synthesis , characterization of dihydrozones derived terazole compounds and evaluation of their biological activity - Sanaa Khalil Ibrahim; Salwa Abdul Sattar Jabbar (Genius Journals, 2023)
This research included the synthesis of new heterocyclic compounds, the compound [S1] was synthesized by the reaction of a carboxylic acid (1,1-biphenyl-4,4'-dicarboxylic acid) with an increase in absolute ethanol and (4-5 ml) of sulfuric acid Center. The compound [S2] was then made by reacting this mixture. The molecule [S1] was combined with aqueous (95%) hydrazine in absolute ethanol, and the hydrazone derivatives [S3-S8] were created by reacting the chemical [S2] created in the second phase with a few benzaldehyde replacements in absolute ethanol. Tetrazole derivatives [S9-S14] were produced by reacting the sodium azide-prepared hydrazones [S3-S9] with tetrahydrofuran in an acidic medium. After the product had been thoroughly cleaned, the synthetic compounds were identified using spectral techniques like UV-Vis, FTIR, 1H, 13C-NMR,, Additionally, utilizing TLC to trace the course of the reactions and evaluate the resulting compounds' melting and purity levels. Two types of bacterial isolates known to be resistant to antibiotics, Pseudomonas aeruginosa, which tested negative for Gram stain [Gr-ve], and Staphylococcus aurous, which tested positive for Gram stain [Gr + ve], were examined for how some prepared compounds affected the growth using the antibiotics amoxicillin and ampicillin. The composition of chemicals produced at the lower energy level was also studied. The studied microorganisms were successfully inhibited by some of the produced chemical substances
Keywords: hydrazones; tetrazole; biphenyl